Lecturas, malas lecturas y parodias: desplumando al cisne rubendariano (Enrique González Martínez, Delmira Agustini, Vicente Huidobro, Nicanor Parra) - Binns, Niall (Anales de Literatura Hispanoamericana, 1995)
Sin resumen